Short-term effects of cold spells on hematocrit among adults in Nanjing, China: A distributed-lagged effect analysis - Cheng, Bei-Jing; Li, Tian-Lin; Li, Hui; Meng, Ke; Meng, Xing-Chen; Wang, Jia; Wang, Chun; Yang, Lin-Sheng; Zhu, Xin-Yi; Liu, Ran (The Science of the total environment, 2023)
Previous studies have linked exposure to cold spells with cardiovascular diseases, however, underlying mechanisms remained to be understood. We aimed to explore the short-term effects of cold spells on hematocrit, a blood indicator associated with cardiovascular disease. Our study was performed among 50,538 participants (68,361 health examination records) who visited the health examination centers of Zhongda Hospital in Nanjing City, China, during the cold seasons from 2019 to 2021. Data on meteorology and air pollution were obtained from the China Meteorological Data Network and the Nanjing Ecological Environment Bureau, respectively. Cold spells in this study were defined as daily mean temperatures (Tmean) <3rd or 5th percentile with two or more consecutive days. Linear mixed-effect models combined with distributed lag nonlinear models were applied to estimate associations of cold spells with hematocrit. Cold spells were found to be significantly correlated with increased hematocrit on lag 0 to 26 days. Moreover, the cumulative effects of cold spells on hematocrit remained significant at varying lag days. These single and cumulative effects were robust across different definitions of cold spells and conversions of hematocrit. For instance, cold spells (Tmean <3rd percentile) at lags 0, 0–1, and 0–27 days were significantly associated with 0.09 [95 % confidence interval (CI): 0.03, 0.15], 0.17 (95 % CI: 0.07, 0.28), and 3.71 (95 % CI: 3.06, 4.35) − unit (%) increases in original hematocrit, respectively. In subgroup analyses, stronger effects of cold spells on hematocrit were observed in females and participants aged 50 years or over. Cold spells have significant immediate and longer-lagged effects (up to 26 days) on hematocrit. Females and individuals aged 50 years or over are more sensitive to cold spells. These findings might provide a new perspective for exploring the effects of cold spells on adverse cardiac events. [Display omitted] •Cold spells have significant immediate and longer-lagged effects on hematocrit.•Females are more sensitive to cold spells.•Individuals aged 50 years or over should be tightly concerned during cold spells.